2022
DOI: 10.1093/stcltm/szac032
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of MSC Cell Therapies for Hospitalized Patients with COVID-19: A Systematic Review and Meta-Analysis

Abstract: MSC (a.k.a. mesenchymal stem cell or medicinal signaling cell) cell therapies show promise in decreasing mortality in acute respiratory distress syndrome (ARDS) and suggest benefits in treatment of COVID-19-related ARDS. We performed a meta-analysis of published trials assessing the efficacy and adverse events (AE) rates of MSC cell therapy in individuals hospitalized for COVID-19. Systematic searches were performed in multiple databases through November 3, 2021. Reports in all languages, including randomized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…However, there is still a significant risk of death in the 20% of patients who develop severe COVID-19 or even acute respiratory distress syndrome (ARDS) ( 41 ). There is evidence that MSC cell therapy has the potential to reduce all-cause mortality and improve pulmonary function ( 42 ). UC-MSC is thought to have stronger angiogenic ( 43 ) and immunomodulatory properties ( 44 ), which may be more relevant to COVID-19-induced pulmonary damage and dysregulated immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is still a significant risk of death in the 20% of patients who develop severe COVID-19 or even acute respiratory distress syndrome (ARDS) ( 41 ). There is evidence that MSC cell therapy has the potential to reduce all-cause mortality and improve pulmonary function ( 42 ). UC-MSC is thought to have stronger angiogenic ( 43 ) and immunomodulatory properties ( 44 ), which may be more relevant to COVID-19-induced pulmonary damage and dysregulated immune response.…”
Section: Discussionmentioning
confidence: 99%
“…First, although this analysis supported that UC-MSC therapy reduces mortality in patients with severe COVID-19, it was important to note that SARS-CoV-2 Variants of Interest (VOIs) were not involved in our included studies, so it was not known whether UC-MSC had a therapeutic effect on VOIs as well. In addition, The conclusions were drawn from a comparison of UC-MSC with earlier standard care and did not take into account new treatments and vaccinations ( 55 ). Recently, numerous studies had confirmed that vaccination reduces mortality in patients with COVID-19 ( 56 ), and further validation is needed to determine whether the vaccine interacts with UC-MCS therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One such use that has been rapidly expanding has been the use of MSCs on patients recovering from COVID-19. Similar to the use of MSCs in autoimmune diseases, those suffering from COVID-19 had no adverse effects from cell transplantation and also had improved lung function, likely resulting from an attenuation of the cytokine storm post SARS-CoV-2 infection [98,99]. Therefore, it may be feasible to ultimately develop a standardized MSC therapy for subgroups of patients, as more studies involving cohorts with defined age and sex information, as well as standardized molecular and cellular measurements, emerge.…”
Section: Discussionmentioning
confidence: 99%
“…[ 147 ] Lastly, clinical trials carried out lack a single standard methodology to be compared with each other. [ 126b,148 ] Despite these drawbacks, these studies hold promise for MSCs as a therapeutic option for the management of COVID‐19‐induced T1DM and T2DM.…”
Section: Mesenchymal Stem Cell‐based Therapeutic Interventions For Th...mentioning
confidence: 99%